Correlation and Capacity Calculations with Reference Antennas in an Isotropic Environment - Thorkild B. Hansen (International Journal of Antennas and Propagation)
A reverberation chamber is a convenient tool for over-the-air testing of MIMO devices in isotropic environments. Isotropy is typically achieved in the chamber through the use of a mode stirrer and a turntable on which the device under test (DUT) rides. The quality of the isotropic environment depends on the number of plane waves produced by the chamber and on their spatial distribution. This paper investigates how the required sampling rate for the DUT pattern is related to the plane-wave density threshold in the isotropic environment required to accurately compute antenna correlations. Once the plane-wave density is above the threshold, the antenna correlation obtained through isotropic experiments agrees with the antenna correlation obtained from the classical definition, as has been proven theoretically. This fact is verified for the good, nominal, and bad reference antennas produced by CTIA. MIMO channel capacity simulations are performed with a standard base station model and the DUT placed in a single-tap plane-wave reverberation chamber model. The capacity curves obtained with the good, nominal, and bad reference antennas are clearly distinguishable.